The Effect of Long-Term Orientation, Power Distance, and Uncertainty Avoidance on Youth Entrepreneurial Orientation in Bandar Lampung - Purnomo, Agus; Oktaviannur, Moh.; Defrizal; Jamaludin, Maun (School of Business, IPB University (SB-IPB), 2024)
Background: As Indonesia's economy is increasingly driven by youth entrepreneurship and innovation, it requires examination of cultural factors and government support to foster entrepreneurial spirit among young people.Purpose: This research empirically investigates the relationship between long-term orientation, power distance, and uncertainty avoidance and how these factors influence the entrepreneurial orientation of young individuals in Bandar Lampung, with the perception of government regulations playing a mediating role. Design/methodology/approach: The study used a quantitative research approach, employing Structural Equation Modeling. The sample consisted of 200 respondents, young entrepreneurs from Bandar Lampung, selected through a simple random sampling method. The analysis was conducted using the Structural Equation Modeling (SEM) approach with the Partial Least Squares (PLS-SEM) technique. Findings/Result: The study found that long-term orientation significantly impacts entrepreneurial orientation. Additionally, it found that power distance and uncertainty avoidance are significant factors in shaping entrepreneurial orientation. Testing the mediating effect of the perception of government regulations indicates a significant role in the relationship between the independent variables and entrepreneurial orientation. The findings of this research indicate that the entrepreneurial mindset of the young generation in Indonesia is moderately influenced by a well-organized environment. Conclusion: The findings underscore the importance of a supportive regulatory environment in fostering entrepreneurial mindset among the youth, prompting policymakers to focus on enhancing regulations to incentivize innovation and streamline procedures for young entrepreneurs.Originality/value (State of the art): The originality of this research lies in its exploration of the interplay between cultural dimensions and government regulations on entrepreneurial orientation, which contributes to the understanding of how socio-cultural factors and regulatory perceptions influence entrepreneurial behavior in emerging economies. Keywords: entrepreneurial orientation, long-term orientation, power distance, uncertainty avoidance, perception of government regulations